• Matéria: Matemática
  • Autor: franklincaldei
  • Perguntado 9 anos atrás

Reescreva a equação (x+3)²=2x(x+7) na forma ax²+bx+c =0

Respostas

respondido por: Anônimo
4

             (x + 3)² = 2x(x + 7)

 Efetuando
                 x² + 6x + 9 = 2x² + 14x

Reduzindo termos semelhantes
              x² - 2x² + 6x - 14x + 9 =0
                  - x² - 8x + 9 = 0

Tdodo x (- 1)
                      x² + 8x - 9 = 0      ECUAÇÃO
                                                   a = 1
                                                   b = 8
                                                   c = - 9
Perguntas similares